Prevalence and determinants of severe acute malnutrition among children under five in Kisangani, Democratic Republic of the Congo - Botela, Charlotte Ponea; Okenge, Léon Ngongo; Mulamba, Emile; Mukandu, Félicien Léyka Basua Babintu; Lumanisha, Junior Kithenge; Mawunu, Monizi; Koto-Te-Nyiwa Ngbolua, Jean-Paul (Orapuh Journal, 2025)
IntroductionMalnutrition remains a major cause of morbidity and mortality among children under five in Kisangani, with Severe Acute Malnutrition (SAM) posing serious threats to survival and development. Ongoing ethnic conflicts in some municipalities exacerbate these risks.PurposeThis study aimed to assess the nutritional status of children under five in Kisangani and identify key risk factors to inform targeted interventions.MethodsA cross-sectional mixed-methods study was conducted from May to July 2025 among 913 children under five years of age. Quantitative data were collected using structured questionnaires on KoboCollect and analysed with ENA and SPSS version 27. Qualitative insights from focus group discussions and key informant interviews were coded and analysed with Atlas.ti to explore feeding practices and conflict-related vulnerabilities.ResultsThe prevalence of SAM was 15.1%. Exclusive breastfeeding was low (7%), and only 5% of children consumed more than five food groups per day. Multivariate analysis identified significant determinants of SAM: children residing in Makiso-Kisangani (OR = 2.53; 95% CI [1.55, 3.49]; p = .004) and Lubunga (OR = 1.89; 95% CI [1.11, 3.21]; p = .019) had higher odds of SAM. Children aged 12–23 months were at increased risk (OR = 1.61; 95% CI [1.01, 2.57]; p = .044), refugees in foster care had elevated risk compared to indigenous children (OR = 2.32; 95% CI [1.55, 3.49]; p < .001), and those living in households with more than 11 members were more likely to be affected (OR = 1.92; 95% CI [1.11, 3.32]; p = .020).ConclusionChildren in Kisangani remain highly vulnerable to malnutrition, largely due to inadequate infant feeding practices and conflict-driven household vulnerabilities. Immediate interventions to improve feeding practices and integrate conflict-sensitive measures are urgently needed to reduce malnutrition-related morbidity and mortality.